Innovative Technologies As A Factor In Developing Students' Information Technological Competence - Usanov Mehriddin Mustafayevich; Qodirov Bekmurod Nurillayevich (Genius Journals, 2025)
Today, the modernization of vocational education, the requirements of employers to graduates of modern universities, the application of new educational technologies in the process of training future professionals, taking into account the competition in the labor market.
Keywords: student; competitiveness; innovative learning technologies